Production process monitoring and post-production mechanical testing of a full-size carbon-fibre composite aircraft tailcone assembly using embedded optical fibre sensors - James, Stephen W.; Tatam, Ralph P.; Staines, Stephen; Chehura, Edmon (Cranfield University, 2021)
The spreadsheet contains the data underpinning the figures within the paper "Production process monitoring and post-production mechanical testing of a full-size carbon-fibre composite aircraft tailcone assembly using embedded optical fibre sensors", Edmon Chehura et al 2020 Meas. Sci. Technol. 31 105204.
Keywords: optical fibre sensors'; 'fibre bragg grating'; 'fresnel refractometer'; 'composite materials'; 'cure monitoring'; 'infusion monitoring'; 'structural monitoring'; 'aircraft tailcone'; 'Aerospace Materials'; 'Aerospace Structures'; 'Composite and Hybrid Materials'; 'Manufacturing Processes and Technologies (excl. Textiles)'; 'Photonics and Electro-Optical Engineering (excl. Communications)'